Analisis ANALISIS ASPEK KOGNITIF DAN EFIKASI DIRI MELALUI IMPLEMENTASI ASESMEN DIAGNOSTIK PADA MATERI USAHA DAN ENERGI DI KELAS VIII SMP NEGERI 4 TAMBANG - Putri, Nadira Rizal; Zulhelmi, Zulhelmi (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This study aims to determine students' cognitive ability and self-efficacy level through diagnostic assessment of business and energetic material in grade VIII SMP Negeri 4 Tambang. This research is a survey research with a quantitative approach. Data was collected by administering test instruments for cognitive diagnostic assessment questions on effort and energy material consisting of 20 multiple-choice question items and self-efficacy questionnaires consisting of 30 statement items. The collected result data is then analyzed using descriptive analysis. Descriptive analysis is used to obtain students' cognitive abilities and self-efficacy in science learning. The results of the descriptive analysis showed that students' cognitive abilities in the cognitive diagnostic assessment of students in class VIII business and energy material of SMP Negeri 4 Tambang were included in the good category with an average score of 51.80. Meanwhile, the results of the self-efficacy analysis of grade VIII students of SMP Negeri 4 Tambang are included in the high category with an average score of 3.32. For this reason, researchers recommend teachers conduct cognitive and non-cognitive diagnostic assessments periodically to determine the level of student abilities and various student conditions.